2011
DOI: 10.1055/s-0030-1270528
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expressions of Ghrelin, PYY, and CCK in the Gastrointestinal Tract of the Hyperphagic Intrauterine Growth Restriction Rat Offspring

Abstract: Intrauterine growth restriction (IUGR) is associated with a substantially greater incidence of metabolic syndrome in adulthood. Animal studies have shown that IUGR offspring are hyperphagic during the early postnatal period and therefore exhibit obesity. The molecular mechanisms underlying food intake regulation in the gastrointestinal tract have not been clarified in IUGR. In the present study, we utilized a rat model of IUGR by restricting the food intake of the mother (50% of the normal intake, ad libitum; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It has been suggested that prenatal growth as well as growth during early infancy may influence the appetite regulatory system by programming appetite regulatory hormones, such as an orexigenic (ghrelin) and an anorexigenic (peptide tyrosine-tyrosine; PYY). Animal studies have supported this hypothesis, showing that postnatal growth retardation has an effect on appetite regulation ( 7 9 ) and that the prevention of immediate rapid newborn catch-up growth may reduce the risk of obesity ( 10 , 11 ) . In addition, an epidemiological study of young adolescents has found an association between rapid early growth and the elevated fasting concentration of ghrelin ( 12 ) .…”
mentioning
confidence: 96%
“…It has been suggested that prenatal growth as well as growth during early infancy may influence the appetite regulatory system by programming appetite regulatory hormones, such as an orexigenic (ghrelin) and an anorexigenic (peptide tyrosine-tyrosine; PYY). Animal studies have supported this hypothesis, showing that postnatal growth retardation has an effect on appetite regulation ( 7 9 ) and that the prevention of immediate rapid newborn catch-up growth may reduce the risk of obesity ( 10 , 11 ) . In addition, an epidemiological study of young adolescents has found an association between rapid early growth and the elevated fasting concentration of ghrelin ( 12 ) .…”
mentioning
confidence: 96%
“…We first hypothesized that gene expression as well as the basal and postprandial release of those peptides may be altered in LP rats. A previous study reported elevated plasma ghrelin and reduced CCK and PYY in adult IUGR rats obtained by a 50%-caloric restriction of their dams diet during gestation and maintained restricted during lactation (37). These changes were paralleled to mRNA levels in gastric and intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased postnatal ghrelin likely plays a role in the rapid catch-up growth observed in most models of gestational programming. In rodents, 50% maternal food restriction during the second half of gestation results in LBW pups that, like human LBW infants, have significantly increased ghrelin expression (Cortelazzi et al, 2003 ; Nagata et al, 2011 ). These animals develop hyperphagia and obesity and demonstrate that catch-up growth among LBW offspring results in programmed elevation of plasma ghrelin levels (reviewed by Breton, 2013 ).…”
Section: Gestational Programming Of Ingestive Behaviormentioning
confidence: 99%